1980
DOI: 10.1159/000123111
|View full text |Cite
|
Sign up to set email alerts
|

Paraventricular Nucleus:A Site for the Integration of Neuroendocrine and Autonomic Mechanisms

Abstract: We have summarized here recent evidence that clarifies the cellular organization and connections of the paraventricular nucleus of the hypothalamus (PVH) in the rat. The nucleus consists of a magnocellular division, with three distinct parts, and a parvocellular division with five distinct parts. Most neurons in the magnocellular division contain either oxytocin or vasopressin, and project to the posterior lobe of the pituitary gland. Separate cell populations centered in the parvocellular division give rise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
482
6
5

Year Published

1984
1984
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 926 publications
(512 citation statements)
references
References 53 publications
19
482
6
5
Order By: Relevance
“…This pathway bypasses classical anatomical units of ascending sensory pathways (spinal, thalamic, and somatosensory cortical nodes) to express post‐traumatic vigilance. At the molecular level, and alike the HPA axis, CRH (Swanson & Sawchenko, 1980), secretagogin (Romanov et al , 2015), and NE (Korf et al , 1973) are used as mediators yet through the recruitment of novel cellular interactions for effective modulation of mPFC output. Moreover, our results suggest that CRH neurons might simultaneously orchestrate HPA activation and cortical excitability, which can be an advantage to overcome metabolic restrictions at the periphery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway bypasses classical anatomical units of ascending sensory pathways (spinal, thalamic, and somatosensory cortical nodes) to express post‐traumatic vigilance. At the molecular level, and alike the HPA axis, CRH (Swanson & Sawchenko, 1980), secretagogin (Romanov et al , 2015), and NE (Korf et al , 1973) are used as mediators yet through the recruitment of novel cellular interactions for effective modulation of mPFC output. Moreover, our results suggest that CRH neurons might simultaneously orchestrate HPA activation and cortical excitability, which can be an advantage to overcome metabolic restrictions at the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, central stress pathways, efficiently linking the brain and periphery, have evolved to form the hypothalamus–pituitary–adrenal axis (HPA) (Selye & Fortier, 1949; Bale & Vale, 2004; McEwen, 2008). By principle, corticotropin‐releasing hormone (CRH)‐containing( + ) neurons of the paraventricular hypothalamic nucleus (PVN) gate output from the central nervous system (Swanson & Sawchenko, 1980) with CRH (Swanson et al , 1983, 1986), through pituitary amplification steps, triggering corticosteroid release from the adrenal glands for immediate metabolic mobilization (Rivier & Vale, 1983; Kovacs & Sawchenko, 1996). Nevertheless, stress, whether due to, e.g., predation or competition for reproduction, is unlikely a singular event.…”
Section: Introductionmentioning
confidence: 99%
“…Neurons of the hypothalamic paraventricular nucleus (PVN) control many important homeostatic functions, including release of pituitary hormones (Swanson 1991;Swanson and Sawchenko 1980;Vigas 1989) and regulation of ingestive behavior/metabolism (Konturek et al 2005;Valassi et al 2008). Over the past several years, studies have increasingly focused on the role of PVN neurons in regulating sympathetic nerve activity (SNA) (Akine et al 2003;Allen 2002;Li and Pan 2007;Li et al 2006;Lovick and Coote 1988b;Porter and Brody 1985;Stern 2004;Toney et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…One group monosynaptically targets the spinal intermediolateral cell column (IML; PVN-IML), the location of sympathetic preganglionic neurons (Saper et al 1976;Swanson and Sawchenko 1980). Another group innervates presympathetic neurons in the rostral ventrolateral medulla (RVLM; PVN-RVLM) (Pyner and Coote 2000;Shafton et al 1998;Stocker et al 2006;Swanson and Sawchenko 1980). A third and more recently identified group has branched axons that innervate both the RVLM and IML (PVN-RVLM/IML) (Pyner and Coote 2000;Shafton et al 1998;Stocker et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate excites the hypothalamic paraventricular nucleus (Boudaba et al, 1997;Li et al, 2004), which has been considered to be the control center of the sympatho-adrenomedullary outflow (Swanson and Sawchenko, 1980;Jansen et al, 1995;Kenny et al, 2003). Previously, we reported that N-methyl-Daspartate applied into this nucleus using dialysis probe elicited concomitant overflow of hypothalamic thromboxane B 2 (a stable metabolite of thromboxane A 2 ) with the elevation of plasma noradrenaline and adrenaline in rats .…”
Section: Discussionmentioning
confidence: 99%